2000
DOI: 10.1111/j.1365-313x.2000.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

AtSUC3, a gene encoding a new Arabidopsis sucrose transporter, is expressed in cells adjacent to the vascular tissue and in a carpel cell layer

Abstract: Summary The cDNA corresponding to the open reading frame T17M13.3 from Arabidopsis chromosome II was isolated and the encoded protein was characterized as a member of a subgroup of higher plant sucrose transporters. The AtSUC3 (Arabidopsis thaliana sucrose transporter 3) open reading frame encodes a protein with 594 amino acid residues, being 81 and 82 residues longer than the previously described Arabidopsis sucrose carriers AtSUC1 and AtSUC2. About 50 of these additional amino acids are part of an extended c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…However, subsequent studies have questioned this hypothesis by finding that null mutations in AtSUC3 have no obvious phenotype and that AtSUC3 protein has measurable biochemical activity (Meyer et al, 2000;Barth et al, 2003). Interestingly, the gene is expressed in many sink tissues and is strongly induced by wounding (Meyer et al, 2000(Meyer et al, , 2004. The only report characterizing a group 3 SUT in grasses showed that the rice OsSUT4 gene is expressed in all tissues examined, although at higher levels in sink leaves (Aoki et al, 2003).…”
Section: Group 3 4 and 5 Sut Family Membersmentioning
confidence: 98%
See 1 more Smart Citation
“…However, subsequent studies have questioned this hypothesis by finding that null mutations in AtSUC3 have no obvious phenotype and that AtSUC3 protein has measurable biochemical activity (Meyer et al, 2000;Barth et al, 2003). Interestingly, the gene is expressed in many sink tissues and is strongly induced by wounding (Meyer et al, 2000(Meyer et al, , 2004. The only report characterizing a group 3 SUT in grasses showed that the rice OsSUT4 gene is expressed in all tissues examined, although at higher levels in sink leaves (Aoki et al, 2003).…”
Section: Group 3 4 and 5 Sut Family Membersmentioning
confidence: 98%
“…Based on sequence characteristics and an initial report of a lack of transport activity, it was postulated that AtSUT2/AtSUC3 might function as a Suc sensor . However, subsequent studies have questioned this hypothesis by finding that null mutations in AtSUC3 have no obvious phenotype and that AtSUC3 protein has measurable biochemical activity (Meyer et al, 2000;Barth et al, 2003). Interestingly, the gene is expressed in many sink tissues and is strongly induced by wounding (Meyer et al, 2000(Meyer et al, , 2004.…”
Section: Group 3 4 and 5 Sut Family Membersmentioning
confidence: 99%
“…SUC1 expression is highly dynamic at the transcriptional level (Vaughn et al, 2002;Li et al, 2003;Sivitz et al, 2008;Zhou et al, 2009); thus, regulation of SUC1 expression might represent a target for ethylene. Transcript levels were examined for four SUC genes, SUC2, -3, and -4 in addition to SUC1, which are expressed at the seedling stage, as well as in the adult leaves (Gottwald et al, 2000;Meyer et al, 2000;Weise et al, 2000), where anthocyanin accumulation is observed (Supplemental Fig. S2A).…”
Section: Transcript Levels Of Suc Transporters In Col0 and Ethylene Amentioning
confidence: 99%
“…SUC1 is expressed in roots, pollen, and trichomes (Sivitz et al, 2008). SUC2 and SUC4 are thought to be involved in Suc loading in companion cells (Gottwald et al, 2000) and minor veins (Meyer et al, 2000;Weise et al, 2000), respectively. SUC3 (SUT2) has been characterized as a weak low-affinity transporter .…”
mentioning
confidence: 99%
“…PCR amplification was carried out with 35 cycles of 2 min at 94 °C, 10 s at 98 °C, 30 s at 56 °C, and 45 s at 68 °C with KOD-Plus-Neo (TOYOBO, Japan). The PCR product was double digested using EcoR I and Sal I and subsequently subcloned into the Saccharomyces cerevisiae/Escherichia coli shuttle vector pEX-Tag (Meyer et al, 2000), which was also doubledigested by EcoR I and Sal I. The recombinant plasmid was transformed into the E. coli strain and sequenced by the Sanger method.…”
Section: Sequence Cloning and Nucleotide Polymorphism Analysesmentioning
confidence: 99%